1968
DOI: 10.1530/jrf.0.0160223
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine-Nucleotide Coenzymes in Bull and Rabbit Spermatozoa

Abstract: Summary. The content of the two pyridine-nucleotide coenzymes, namely nicotinamide adenine dinucleotide (NAD) and nicotinamide adenine dinucleotide phosphate (NADP), has been determined in bull and rabbit spermatozoa, using the enzymic-fluorimetric procedure of Bassham, Birt, Hems & Loening (1959). It has been found necessary to wash spermatozoa thoroughly before extraction, so as to remove all traces of seminal plasma enzymes which otherwise would have degraded the coenzymes in the course of the analytical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

1970
1970
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
(7 reference statements)
3
7
1
Order By: Relevance
“…Bistocchi et al (1968) showed that ejaculated bull spermatazoa possessed less than 35 % of the levels of NAD and NADP found in epididymal spermatazoa. It has not been resolved whether NAD and NADP are hydrolysed by the same enzyme which cleaves the ribosyl pyridinium bond.…”
Section: Introd:uctionmentioning
confidence: 99%
“…Bistocchi et al (1968) showed that ejaculated bull spermatazoa possessed less than 35 % of the levels of NAD and NADP found in epididymal spermatazoa. It has not been resolved whether NAD and NADP are hydrolysed by the same enzyme which cleaves the ribosyl pyridinium bond.…”
Section: Introd:uctionmentioning
confidence: 99%
“…Macmillan (1973) concluded that sire differences in conception rate primarily involved variation in the duration of post-insemination sperm liveability. Bistocchi et al (1968) showed that after 4 h incubation at 37°C ejaculated bull sperm contained less than 2 Jlmol of total nucleotides per 10 9 sperm compared to at least 10 Jlmol in incubated epididymal sperm. This difference in concentration largely arose through the destruction of most of the nucleotides measured in epididymal sperm by the nucleosidase, this effect occurring within 1 min of ejaculation.…”
Section: Discussionmentioning
confidence: 97%
“…The enzyme destroys most of the oxidized pyridine nucleotide coenzymes measured in washed epididymal sperm within 1 min of ejaculation (Bistocchi et al 1968). These coenzymes are important for the maintenance of motility and the metabolism of spermatazoa (Brookes and Mann 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of nicotinamide coenzymes expressed in nmol./10 9 sperm vary between species (Brooks & Mann 1971) and between epididymal and ejaculated sperm within species (Bistocchi et al 1968). Nicotinamide adenine dinucleotide glycohydrolase (EC 3.2.2.5) has been purified from bull semen (Yuan & Anderson 1971) and is most likely the pyridine nucleosidase that hydrolyses over 60 percent of the NAD and NAD P possessed by bovine epididymal sperm within minutes of ejaculation (Bistocchi et al 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotinamide adenine dinucleotide glycohydrolase (EC 3.2.2.5) has been purified from bull semen (Yuan & Anderson 1971) and is most likely the pyridine nucleosidase that hydrolyses over 60 percent of the NAD and NAD P possessed by bovine epididymal sperm within minutes of ejaculation (Bistocchi et al 1968).…”
Section: Introductionmentioning
confidence: 99%